Time Out of Joint and Future-Oriented Memory: Engaging Dietrich Bonhoeffer in the Search for a Way to Deal Responsibly with the Ghosts of the Past - Vosloo, Robert Roux (Religions, 2017)
This article explores in conversation with some of the writings of Dietrich Bonhoeffer the question of how the experience of the dislocation of time and the visitation of the ghosts of the past (also in contexts marked by historical injustices) is related to responsible ethical action. The question is also posed as to how the reconfiguration of the relationship of past, present and future functions on an implicit and explicit level in this regard. In the process, the article affirms the eschatological horizon of Bonhoeffer's ethics and points to the importance of what is referred to as future-oriented memory in the search for responsible and hopeful action. The article acknowledges the dilemmas in relating thought and action (with reference to the so-called Hamlet doctrine) and points to the way in which the future marks and determines Bonhoeffer's understanding of ethical action amidst the haunting presence of the past and the experience of the present time as a time out of joint.